Di’ao Xinxuekang Capsule Improves the Anti-Atherosclerotic Effect of Atorvastatin by Downregulating the SREBP2/PCSK9 Signalling Pathway - Liang, Jiyi; Li, Wei; Liu, Honglin; Li, Xiaofen; Yuan, Chuqiao; Zou, Wenjun; Qu, Liping (Frontiers in Pharmacology, 2022)
Statins are the first choice for lowering low-density lipoprotein cholesterol (LDL-C) and preventing atherosclerotic cardiovascular disease (ASCVD). However, statins can also upregulate proprotein convertase subtilisin/kexin type 9 (PCSK9), which in turn might limits the cholesterol-lowering effect of statins through the degradation of LDL receptors (LDLR). Di’ao Xinxuekang (DXXK) capsule, as a well-known traditional Chinese herbal medicine for the prevention and treatment of coronary heart disease, can alleviate lipid disorders and ameliorate atherosclerosis in atherosclerosis model mice and downregulate the expression of PCSK9. In this study, we further explored whether DXXK has a synergistic effect with atorvastatin (ATO) and its underlying molecular mechanism. The results showed that both ATO monotherapy (1.3 mg/kg) and ATO combined with DXXK therapy significantly lowered serum lipid levels and reduced the formation of atherosclerotic plaques and the liver lipid accumulation. Moreover, compared with ATO monotherapy, the addition of DXXK (160 mg/kg) to the combination therapy further lowered LDL-C by 15.55% and further reduced the atherosclerotic plaque area by 25.98%. In addition, the expression of SREBP2, PCSK9 and IDOL showed a significant increase in the model group, and the expression of LDLR was significantly reduced; however, there were no significant differences between the ATO (1.3 mg/kg) and the model groups. When ATO was combined with DXXK, the expression of LDLR was significantly increased and was higher than that of the model group and the expression of SREBP2 and PCSK9 in the liver was also significantly inhibited. Moreover, it can be seen that the expression of SREBP2 and PCSK9 in the combination treatment group was significantly lower than that in the ATO monotherapy group (1.3 mg/kg). Besides, the expression of IDOL mRNA in each treatment group was not significantly different from that of the model group. Our study suggests that DXXK might have a synergistic effect on the LDL-C lowering and antiatherosclerosis effects of ATO through the SREBP2/PCSK9 pathway. This indicates that a combination of DXXK and ATO may be a new treatment for atherosclerosis.